A fully abstract model for the exchange of information in multi-agent systems - de Boer, Frank S.; van Eijk, Rogier M.; van der Hoek, Wiebe; Meyer, John-Jules Ch (Theoretical computer science, 2003)
In this paper,11This paper is an extended version of [7]. we present a semantic theory for the exchange of information in multi-agent systems. We consider the multi-agent programming language agent communication programming language, which integrates the paradigms of concurrent constraint programming and communicating sequential processes (CSP). The constraint programming techniques are used to represent and process information, whereas the synchronous communication mechanism from CSP is generalised to enable the exchange of information. The semantics of the language, which is based on a generalisation of traditional failure semantics, is shown to be fully abstract with respect to observing of each terminating computation its final global store of information.